2015
DOI: 10.1007/s40011-015-0607-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Waterlogging on Element Concentrations, Growth and Yield of Wheat Varieties Under Farmer’s Sodic Field Conditions

Abstract: Six promising waterlogging tolerant varieties of wheat along with two local varieties were evaluated on farmer's sodic field (pH, 8.9) under drained and waterlogged conditions. Waterlogging was imposed for 12 days at 25 days after sowing. The redox potential (Eh) value of the soil was reduced to ?90 mV at 12 days of waterlogging and after removal of surface water, 16 days were taken to reach above the anoxic limit (B?350 mV) of soil. Waterlogging reduced significantly the shoot dry weight of all varieties, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 23 publications
6
17
0
Order By: Relevance
“…Waterlogging decreases P content because of oxygen deficiency and impaired root functioning (Trought and Drew, 1980) and lack of energy for ion uptake (Barrett-Lennard et al, 1990). Similar to our results, decline in P content have been reported for waterlogged wheat and sensitive varieties of wheat have lower P content than tolerant varieties (Huang et al,1995;Singh and Setter, 2017). The leaf K content under waterlogging dropped below the critical ( ) deficiency level (Anderson and Bowen, 1990;McCray and Mylavarapu, 2010), except for varieties CoLk 94184, CoS 767 and CoLk 12202 (Fig.…”
Section: O N L I N E C O P Ysupporting
confidence: 90%
See 2 more Smart Citations
“…Waterlogging decreases P content because of oxygen deficiency and impaired root functioning (Trought and Drew, 1980) and lack of energy for ion uptake (Barrett-Lennard et al, 1990). Similar to our results, decline in P content have been reported for waterlogged wheat and sensitive varieties of wheat have lower P content than tolerant varieties (Huang et al,1995;Singh and Setter, 2017). The leaf K content under waterlogging dropped below the critical ( ) deficiency level (Anderson and Bowen, 1990;McCray and Mylavarapu, 2010), except for varieties CoLk 94184, CoS 767 and CoLk 12202 (Fig.…”
Section: O N L I N E C O P Ysupporting
confidence: 90%
“…Thus, high leaf K content may be an important selection indices for waterlogging tolerance. Decrease in K in sugarcane varieties under waterlogging is in agreement with the previous report on wheat (Singh and Setter, 2017). It is also suggested that application of potassium along with N and P improves the tolerance to waterlogging (Cong et al, 2009).…”
Section: O N L I N E C O P Ysupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, decreasing molecular oxygen prompts a sequence of changes in the physico-chemical properties of the soil (Ponnamperuma, 1984). Many of these also change soil chemical and electro chemicals by decreasing redox potential and excess electron changes, such as Fe 3+ and Mn 4+ to Fe 2+ and Mn 2+ , correspondingly (Ponnamperuma, 1984; Jackson and Colmer, 2005; Singh and Setter, 2017). Thus, solubility of iron and manganese rises to toxic levels, which are potentially damaging to plant roots (Jones and Etherington, 1970; Aldana et al, 2014; Marashi, 2018; Sharma et al, 2018).…”
Section: Waterlogging Effect On Soil and Plant Growthmentioning
confidence: 99%
“…According to Marschner (2012) soil with redox potential <300 mV has no free O2 and in <250 mV has no NO3available. In saturated water, Singh and Setter (2017) noted the increase in the availability of toxic elements such as Fe, Mn, and Al. Although Sagala et al (2011) noted that continuous flooding inactive Fe toxicity.…”
Section: Plasticity Characters and Its Usefulness In The Cultivation mentioning
confidence: 99%